Unveiling technology’s integral role in pencak silat: A systematic literature review - Sinulingga, Albadi; Kasih, Indra; Hasibuan, Sanusi; Daulay, Dicky Edwar; Abdullah, Nagoor Meera (Journal Sport Area, 2024)
Background Problems: Over the past decade, research on technology in Pencak Silat has grown rapidly. However, the literature review on this topic was very limited. Research Objectives: The purpose of this paper is to conduct an in-depth systematic literature review on the role of technology in the development of Pencak Silat. Methods: Two databases (Scopus and Web of Science) were used to select articles containing information on this topic. The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After the exclusion criteria, only 14 articles were categorised. Findings and Results: Results from the analysed literature showed the positive impact of various technologies on the learning of Pencak Silat and improvements in training and sporting events. The application of technologies such as interactive multimedia, Android applications, augmented reality (AR), and virtual reality (VR) has been shown to improve students' understanding and achievement in understanding the basic and complex movements of Pencak Silat. Likewise, in the world of sports, technologies such as RFID, fuzzy logic, the Internet of Things (IoT), 3D motion capture, sensors, and VR have changed the way training and scoring in Pencak Silat matches were conducted. Conclusion: Technology has played a key role in improving Pencak Silat education and the sport of Pencak Silat. It has brought significant changes in the way movements are understood, training is conducted, and judgement is made. With wise use, technology continues to open up opportunities to better understand Pencak Silat and improve the quality of learning and competition.